2020
DOI: 10.1111/hsc.13065
|View full text |Cite
|
Sign up to set email alerts
|

Community violence and African American male health outcomes: An integrative review of literature

Abstract: The morbidity and mortality rates of African American men consistently rank among the lowest across all groups in the United States. African American men have one of the highest mortality rates for heart disease, cancer, stroke unintentional injuries and homicide (Gilbert et al., 2016). The leading cause of death in African American men age 24-34 years old is homicide (CDC, 2011). A majority of the health disparities experienced by African American men are the result of socioeconomic disadvantage, racism and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…For example, survivors have an increased likelihood of misusing alcohol and drugs as a way of coping and/or self-treating trauma. 8 Sadly, this may even create generational effects, as children of survivors have a greater likelihood of engaging in violent behavior and/or experiencing posttraumatic stress disorder themselves. 9 Taken together, these factors culminate in what is commonly referred to as a "revolving door phenomenon" of community violence.…”
Section: Community Violence Is a Preventable Public Health Issuementioning
confidence: 99%
See 1 more Smart Citation
“…For example, survivors have an increased likelihood of misusing alcohol and drugs as a way of coping and/or self-treating trauma. 8 Sadly, this may even create generational effects, as children of survivors have a greater likelihood of engaging in violent behavior and/or experiencing posttraumatic stress disorder themselves. 9 Taken together, these factors culminate in what is commonly referred to as a "revolving door phenomenon" of community violence.…”
Section: Community Violence Is a Preventable Public Health Issuementioning
confidence: 99%
“…The aftermath of violent injury commonly generates various subsequent risk factors for repeat injuries. For example, survivors have an increased likelihood of misusing alcohol and drugs as a way of coping and/or self-treating trauma 8 . Sadly, this may even create generational effects, as children of survivors have a greater likelihood of engaging in violent behavior and/or experiencing posttraumatic stress disorder themselves 9 .…”
Section: Community Violence Is a Preventable Public Health Issuementioning
confidence: 99%
“…For example, Wright and Colleagues (2017) synthesized the literature on physical health outcomes in youth with CVE and found associations with several adverse conditions like asthma and increased weight. In support of Wright and Colleagues (2017), Thomas and Colleagues (2020) explored CVE’s impact on health outcomes in Black males of all ages and found they were more likely to have traumatic stress, sexually transmitted infections, inflammatory reactions, violence perpetration, and substance use. A third review by Motley and Colleagues (2017) examined risk taking behaviors of Black emerging adults with CVE and found that CVE was associated with substance use.…”
Section: Introductionmentioning
confidence: 99%
“…Pieterse et al [11] and Williams and William-Morris [12] focused on mental health more broadly, while additional reviews focused on the association between discrimination and depressive symptoms in Black men [13] and the association between depressive symptoms and perceived discrimination [14]. Further, Watkins et al [15], Ward and Mengesha [16], and Plowden et al [17] discussed risk factors for depression in African American men, including several SDOH, and more recent studies have highlighted the negative impact of police encounters [18] and community violence on African American male mental health [19]. A different perspective from Reed et al [20] explored social work research on SDOH as protective factors regarding African American suicide.…”
Section: Introductionmentioning
confidence: 99%